Students' preferences for lecturers' personalities: A study among University Malaysia Sabah (UMS) students - Ismail Maakip (Persatuan Psikologi Malaysia, 2008)
Malaysian older adults will be accounted for 10% of the population by 2020 as the consequence of the global ageing demographic revolution. Malaysian studies showed poor quality of life (QOL) among Malaysian older adults despite their long life expectancy. Studies showed the positive relationship between religiosity, spirituality, and QOL. However, previous studies did not distinguish spirituality from religiosity and it has presented insufficient persuasiveness of findings. This study aims to investigate spirituality and religiosity as the predictors for QOL. Quantitative and cross-sectional survey designs were used in this study. 180 participants from aged 60 to 88 were recruited. This study used multiple linear regression analysis to examine the predictors of religiosity and spirituality on QOL. The result showed only spirituality predicted QOL among elderly adults, but not religiosity. The findings of the study implied the importance of internalising spiritual virtues instead of focusing on religious activities which may not improve QOL among older adults significantly.